Methodology and intermediate layer for the automatic creation of ontology instances stored in relational databases. (20th February 2012) - Stanimirović, Aleksandar; Bogdanović, Miloš; Stoimenov, Leonid
SUMMARY: In this paper, we introduce our solution for mapping local ontologies to relational and object‐oriented representations. This solution is part of the GeoNis framework for the interoperability of geo‐information systems applications in a local community environment. The GeoNis framework is based on a hybrid ontology approach for data integration. Therefore, a very important subject in our research on semantic data integration is the creation of mapping between a spatial information source and its local ontology. We developed the OWL2RDB mapping language to create an intermediate layer between a relational database and the OWL ontology. This intermediate layer contains rules (expressed in the OWL2RDB language) for mapping between the structural elements of a relational database and the concepts of OWL ontologies. We also present a system that uses the OWL2RDB intermediate layer to create classes that can handle ontology instances stored in relational databases. We have developed a prototype for a tool that uses this proposed approach for the automatic generation of translator/wrapper components in the GeoNis interoperability environment. Copyright © 2012 John Wiley & Sons, Ltd.